Early prediction of normocalcemia after thyroid surgery - GÜLLÜOĞLU, MAHMUT BAHADIR; YEGEN, ŞEVKET CUMHUR (SPRINGER, 2005)
Hypocalcemia is the principal factor that determines length of hospital stay after thyroid surgery. Seventy-nine patients who underwent thyroidectomy were prospectively evaluated in order to define risk factors for postoperative hypocalcemia. Serum samples were taken postoperatively at 8, 14, 24, and 48 hours to measure total calcium levels. The slope of change in serum calcium level between each sample time was calculated. Patients were also examined for age, gender, surgical indications, type and extension of surgery, thyroid function, presence of substernal extension, initial operation versus reoperation, and application of parathyroid autotransplantation. All comparisons were made between hypocalcemic and normocalcemic groups. Hypocalcemia occured in 15 (19%) patients. In univariate analysis, type and extent of thyroidectomy, serum calcium levels at each time point, as well as the slope of change in serum total calcium levels between 8 and 14 hours were found to be significantly predictive of normocalcemia. All patients who underwent hemithyroidectomy and who had a`positive or neutral slope of calcium change after surgery remained normocalcemic. By multivariate logistic regression analysis, only the slope of change in calcium levels within the first 14 postoperative hours independently predicted calcium status after thyroidectomy. All patients who undergo unilateral thyroid surgery who have a positive/neutral slope of change in serum total calcium levels within the first 14 hours after surgery can be safely discharged early if they have no other risks.
Keywords: HYPOCALCEMIA FOLLOWING THYROIDECTOMY; PARATHYROID-HORMONE LEVELS; SERUM-CALCIUM LEVELS; POSTTHYROIDECTOMY HYPOCALCEMIA; RISK-FACTORS; EXPLORATION; GLAND; ASSAY